Understanding the determinants of postnatal care uptake for babies: A mixed effects multilevel modelling of 2016-18 Papua New Guinea Demographic and Health Survey - Francis Appiah; Justice Ofosu Darko Fenteng; Felix Dare; Tarif Salihu; Andrews Ohene Darteh; Matthew Takyi; Patience Ansomah Ayerakwah; Edward Kwabena Ameyaw (BMC, 2021)
Abstract Background Papua New Guinea (PNG) recorded 22 neonatal deaths out of every 1,000 livebirths in 2019. Some of these deaths are related to complications that arise shortly after childbirth; hence, postnatal care (PNC) utilisation could serve as a surviving strategy for neonates as recommended by the World Health Organisation. National level study on determinants of PNC uptake in PNG is limited. Utilising the Bronfenbrenner's Ecological Model of Human Development, the study aimed at assessing determinants of PNC utilisation for babies by their mothers aged 15-49 in PNG. Methods The study used data from the women's file of the 2016-18 PNG Demographic and Health Survey (2016-18 PNGDHS) and a sample of 4,908 women aged 15-49 who had complete information on the variables of interest to the study. Nineteen (19) explanatory variables were selected for the study whereas PNC for babies within first two months after being discharged after birth was the main outcome variable. At 95% confidence interval (95% CI), six multilevel logistic models were built. The Akaike Information Criterion (AIC) was used to assess models' fit. All analyses were carried out using STATA version 14.0. Results Generally, 31% of the women utilised PNC for their babies. Women with primary education [aOR = 1.42, CI = 1.13-1.78], those belonging to the middle wealth quintile [aOR = 1.42, CI = 1.08-1.87], working class [aOR = 1.28, CI = 1.10-1.49], women who had the four or more ANC visits [aOR = 1.23, CI = 1.05-1.43], those with twins [aOR = 1.83, CI = 1.01-3.29], women who belonged to community of medium literate class [aOR = 1.75, CI = 1.34-2.27] and those of moderate socioeconomic status [aOR = 1.60, CI = 1.16-2.21] had higher odds of seeking PNC for their babies. The odds to seek PNC services for babies reduced among the cohabiting women [aOR = 0.79, CI = 0.64-0.96], those at parity four or more [aOR = 0.77, CI = 0.63-0.93], women who gave birth to small babies [aOR = 0.80, CI = 0.67-0.98] and residents in the Highlands region [aOR = 0.47, CI = 0.36-0.62]. Conclusions Maternal education, wealth quintile, occupation, partner's education, ANC visits, marital status, parity, child size at birth, twin status, community literacy and socioeconomic status as well as region of residence were associated with PNC uptake for babies in PNG. Variation in PNC uptake for babies existed from one community/cluster to the other. There is the need to strengthen public health education to increase awareness about the benefits of seeking PNC services for babies among women in PNG. Such programs should consider maternal and community/cluster characteristics in their design.